Genetic variability, correlation and path analysis in faba bean (Vicia faba) - GUPTA, G C; GUPTA, S N; TOMER, Y S; SINGH, SULTAN (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted to study the variability, correlations and path coefficients for 9 metric traits in 100 faba bean(vicia faba L.)genotypes during winter (rabi) season of 1993 and 1994.Significant genotypic differences were observed for all the traits in both the years. The genetic variability as estimatedby its component parameters like variances and coefficients of variation was high for plant height, pod-bearing length, harvest index, fruiting branches/plant, pods/plant and seed yield/plant.Hight heritability was followed by high genetic advance for the latter 3 characters indicating the scope for their improvement through selection. Seed yield/plant was positively correlated with plant height and phenotypic levels. The harvest index had negatively correlated with days to maturity both at genotypic and penotypic levels. The harvest index had the highest direct effect on seed yield which was followed by pods/plant and 100 seed weight.Plant height and pod bearing length had the highest indirect effect. Plant height,pod bearing length, pods/plant and harvest index were the principal yield attributes.